2024
DOI: 10.3390/nano14050413
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Cell Membrane-Camouflaged Nanomaterials for Biomedical Applications

Xiyuan Guan,
Simin Xing,
Yang Liu

Abstract: Recent strides in nanomaterials science have paved the way for the creation of reliable, effective, highly accurate, and user-friendly biomedical systems. Pioneering the integration of natural cell membranes into sophisticated nanocarrier architectures, cell membrane camouflage has emerged as a transformative approach for regulated drug delivery, offering the benefits of minimal immunogenicity coupled with active targeting capabilities. Nevertheless, the utility of nanomaterials with such camouflage is curtail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 164 publications
0
0
0
Order By: Relevance
“…A significant amelioration of ulcerative colitis and apical periodontitis was obtained by encapsulating curcumin into CXCR4 cell membrane vesicles through physical entrapment. The obtained cell membrane vesicles induced higher M2 macrophage polarization and showed anti-inflammatory effects [ 41 , 42 ]. The anti-inflammatory efficacy of curcumin-loaded nanoparticles has been recently evidenced, as they were able to reduce the expression of Nf-κb, TGF-β1, IL-6, and IL-1β in lipopolysaccharide-inflamed cells, thus suggesting these nanoparticles as possible candidates for the targeted anti-inflammatory therapy of atherosclerosis [ 43 ].…”
Section: Curcumin Nanoparticlesmentioning
confidence: 99%
“…A significant amelioration of ulcerative colitis and apical periodontitis was obtained by encapsulating curcumin into CXCR4 cell membrane vesicles through physical entrapment. The obtained cell membrane vesicles induced higher M2 macrophage polarization and showed anti-inflammatory effects [ 41 , 42 ]. The anti-inflammatory efficacy of curcumin-loaded nanoparticles has been recently evidenced, as they were able to reduce the expression of Nf-κb, TGF-β1, IL-6, and IL-1β in lipopolysaccharide-inflamed cells, thus suggesting these nanoparticles as possible candidates for the targeted anti-inflammatory therapy of atherosclerosis [ 43 ].…”
Section: Curcumin Nanoparticlesmentioning
confidence: 99%
“…Comparing cell membrane-camouflaged drug delivery systems to cell-based drug delivery systems, recent research has revealed that the latter can lose all of the native cells’ biological characteristics and functions, including the long lifespan of erythrocytes (red blood cells, or RBCs) in circulation, the ability of macrophages, neutrophils, and mesenchymal stem cells to homing in on inflammation, and the capacity of T cells and natural killer cells to recognize and eliminate tumors [ 192 , 193 , 194 ]. Additionally to the effect of nanocarriers, various physiological and pathological barriers, such as hepatic metabolism, renal filtration, immune clearance, and various organ and tissue barriers (e.g., epithelial–endothelial barrier, extracellular matrix barrier, and cell membrane barrier), control the drug delivery capabilities of mesenchymal stem cells in vivo [ 195 , 196 ].…”
Section: Biotransformation Mechanisms and Clearance Of Mesenchymal St...mentioning
confidence: 99%